Historical Jesus: A Multidisciplinary Perspective and the Aesthetics in Western Images of the Sacred - Silva Lourenço, Hudson (2025)
This article examines the discrepancy between the historical Jesus and his representations in Western art, aesthetically transformed to reflect European traits. Drawing on the analyses of John P. Meier and thehistorical-critical studies of Antonio Piñero, Fernando Bermejo Rubio, and others, we discuss the ideological role of these images in reinforcing Eurocentric hegemony. Supported by philosophical aesthetics, we argue for the need to reassess these representations in the religious context as well, advocating for an inclusive and historically accurate aesthetic that better reflects cultural diversity and provides a meaningful image of Jesus for marginalized communities.